Answer:
4. (6,0)
Step-by-step explanation:
Plug the points into the equation.
6+3(0)=6
6+0=6
6=6
Answer:
41 + 43? I think
Step-by-step explanation:
41 + 43 = 84
43 - 41 = 2
Step-by-step explanation:
y-2 = - 3(x-3)
y - 2 =-3x +9
y -2 +2 = - 3x +9 +2
y = - 3x +11
To find the the coordinate
When x =0
y = - 3(0) +11
y= 11
When y = 0
0 = - 3x +11
Subtract 11 from both sides
-3x = - 11
x = 11/3
The y intercept is 11 so, one of your points will be at (0, 11) while the other will be at (11/3, 11).
Answer: see proof below
<u>Step-by-step explanation:</u>
Given: A + B + C = π → C = π - (A + B)
→ sin C = sin(π - (A + B)) cos C = sin(π - (A + B))
→ sin C = sin (A + B) cos C = - cos(A + B)
Use the following Sum to Product Identity:
sin A + sin B = 2 cos[(A + B)/2] · sin [(A - B)/2]
cos A + cos B = 2 cos[(A + B)/2] · cos [(A - B)/2]
Use the following Double Angle Identity:
sin 2A = 2 sin A · cos A
<u>Proof LHS → RHS</u>
LHS: (sin 2A + sin 2B) + sin 2C




![\text{Factor:}\qquad \qquad \qquad 2\sin C\cdot [\cos (A-B)+\cos (A+B)]](https://tex.z-dn.net/?f=%5Ctext%7BFactor%3A%7D%5Cqquad%20%5Cqquad%20%5Cqquad%202%5Csin%20C%5Ccdot%20%5B%5Ccos%20%28A-B%29%2B%5Ccos%20%28A%2BB%29%5D)


LHS = RHS: 4 cos A · cos B · sin C = 4 cos A · cos B · sin C 